2016
DOI: 10.1111/emr.12208
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating impacts of weeds and kangaroo grazing following prescribed fire in a Banksia woodland

Abstract: Summary Banksia woodlands are renowned for their flammability and prescribed fire is increasingly employed to reduce the risk of wildfire and to protect life and property, particularly where these woodlands occur on the urban interface. Prescribed fire is also employed as a tool for protecting biodiversity assets but can have adverse impacts on native plant communities. We investigated changes in species richness and cover in native and introduced flora following autumn prescribed fire in a 700‐hectare Banksia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Whilst the non-native grass E. calycina can resprout following fire and return to seed production within the first year after fire, quick post-fire emergence may perpetuate the expansion of E. calycina populations. Such a lifecycle may increase the species cover, and perpetuate the fire-weed cycle, a feature common among many invasive grasses (Brown, Paczkowska, & Gibson, 2016;D'Antonio & Vitousek, 1992).…”
Section: Anigozanthos Manglesiimentioning
confidence: 99%
“…Whilst the non-native grass E. calycina can resprout following fire and return to seed production within the first year after fire, quick post-fire emergence may perpetuate the expansion of E. calycina populations. Such a lifecycle may increase the species cover, and perpetuate the fire-weed cycle, a feature common among many invasive grasses (Brown, Paczkowska, & Gibson, 2016;D'Antonio & Vitousek, 1992).…”
Section: Anigozanthos Manglesiimentioning
confidence: 99%
“…Similarly, Fisher et al (2006Fisher et al ( , 2009aFisher et al ( , 2009b investigated the effects of introduced species seed bank, fire, and soil nutrient status on plant invasion and found that invasive species alter the nutrient composition of soils and create conditions unconducive for native species. The role of fire in promoting invasion was also investigated by Milberg and Lamont (1995), Ruthrof et al (2003), Ruthrof (2004) and Brown et al (2016), among others. Ehrharta calycina Sm.…”
Section: Floristics and Weedsmentioning
confidence: 99%
“…Fuel management should be undertaken within the ecological tolerances of the environment being managed to avoid undesirable effects such as weed invasion, decline in habitat quality or loss of species that have fire-regime specific attributes (Brown et al 2016;Wooller et al 2002;Gosper et al 2013). In principle, the regular occurrence of high-intensity summer bushfire is considered likely to have deleterious effects on biodiversity (Burrows 2013;Bain et al 2016) and environmental values, including water quality and carbon stored in woody biomass (Nunes et al 2018;Volkova et al 2014;Whitford and McCaw 2019).…”
Section: Ecological Requirements Are Considered When Managing Fuelmentioning
confidence: 99%